Implementasi Motif Kain Cual Pada Meja Konter Informasi RSUD Depati Bahrin, Kabupaten Bangka - Nirmala Sari Hayatthien; Irma Damayantie (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hospitals are vital institutions that provide comprehensive healthcare services, including inpatient care, outpatient care, and emergency services. The Depati Bahrin Sungailiat Regional General Hospital, located in the province of Bangka Belitung, strives to highlight local cultural identity in its interior design elements. For this purpose, the information counter desk was selected as the medium for applying the Kembang Setangkai motif from cual fabric, a cultural heritage unique to Bangka Belitung. The counter desk, as the initial point of interaction between visitors and the hospital, is expected to reflect a professional atmosphere while also valuing local wisdom. Using Rosemary Kilmer design method with a focus on the synthesis stage, which includes idea development, concept selection, and design realization. Data was obtained through literature reviews on local culture and observations of information space needs. Two design alternatives for the information counter were developed and analyzed based on visual aspects, functionality, and cultural symbolic value. From the analysis, the second alternative was chosen for its superiority in achieving visual balance, safe and friendly forms, and aesthetically pleasing motif placement. The Kembang Setangkai motif was applied at two points on the counter with a combination of green and natural neutral colors, evoking warmth and tranquility. This design was realized using HPL material and duco paint with ergonomic dimensions in accordance with public service standards. This implementation not only strengthens the image of the RSUD as an institution that upholds local cultural values but also serves as a manifestation of tradition preservation aligned with modern spatial needs.